Prevalence of Cognitive and Vestibular Impairment in Seniors Experiencing Falls. (20th March 2021) - Varriano, Brenda; Sulway, Shaleen; Wetmore, Curtis; Dillon, Wanda; Misquitta, Karen; Multani, Namita; Anor, Cassandra; Martinez, Maria; Cacchione, Elena; Rutka, John; Tartaglia, Maria Carmela
ABSTRACT: Background: Falls are a growing concern in seniors (≥65 yrs). Cognitive impairment (CI) and vestibular impairment (VI) increase fall risk. The aim of this study is to assess the prevalence of CI and VI in seniors experiencing falls. Methods: Participants (≥65 yrs) with falls were recruited from Falls Prevention Programs (FPPs) and a Memory Clinic (MC). CI was assessed using the Montreal Cognitive Assessment at FPPs. VI was assessed at an MC and FFPs using the Head Impulse- (video + bedside), Headshake-, Dix-Hallpike test, and test of sensory interaction in balance. Questionnaires included Dizziness Handicap Inventory (DHI) and Activities-specific Balance Confidence Scale (ABC). Results: Of 41 participants (29 FPPs, 12 MC); mean age was 80.1 ± 7.1 years, and 58.5% were female. Overall, 82.9% had VI. At FPPs, 76.0% had CI, and 72.3% had CI + VI. Bilateral vestibular hypofunction (BVH) was more common than unilateral vestibular hypofunction (UVH) (70.6% vs. 29.4%); p = 0.016. Dizziness Handicap (DHI) was not different between those with a VI (23.5 ± 23.9) versus without VI [PVI + no impairment] (10.0 ± 15.4); p = 0.160. Balance confidence (ABC) was lowest in VI but not significantly different between those with a VI (63.4 ± 27.3) versus without VI [PVI + no impairment] (85.0 ± 16.5); p = 0.053. Conclusions: VI and CI are prevalent in seniors experiencing falls. For seniors with history of falls, both cognitive and vestibular functions should be considered in the assessment and subsequent treatment. Screening enables earlier detection, targeted interventions, and prevention, reducing the clinical and financial impact.